Privacy driven internet ecosystem - Tuan Anh Trinh; Laszlo Gyarmati (International Telecommunications Society (ITS), 2012)
The dominant business model of today's Internet is built upon advertisements; users can access Internet services while the providers show ads to them. Although significant efforts have been made to model and analyze the economic aspects of this ecosystem, the heart of the current status quo, namely privacy, has not received the attention of the research community yet. Accordingly, we propose an economic model of the privacy driven Internet ecosystem where privacy is handled as an asset that can be traded. Expressing the entropy of privacy as the service providers' fitness value and applying a dynamic network formation model based on the preferential attachment principle allow the analysis of the providers' economic interactions in a realistic framework, whose properties are illustrated based on extensive simulations.
Keywords: 330